2016
DOI: 10.1007/s00198-016-3876-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reference curves of volumetric bone density, structure, and biomechanical parameters adjusted for weight and height in a population of healthy women: an HR-pQCT study

Abstract: These data provide reference curves from healthy women and demonstrate that density and structural and biomechanical parameters differ between the radius and tibia and between the trabecular and cortical compartments. In postmenopausal women, the trabecular bone remained relatively stable at the tibia site, whereas the cortical compartment changed significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 43 publications
3
33
0
13
Order By: Relevance
“…First, our results showed that Ct.Th and Ct.Po, as depicted by BDAT, exhibited significant age‐related dependence for women: Concurrent with the increased porosity, the thickness at the radius was reduced with aging. These results are consistent with data obtained previously with HRpQCT . Second, Ct.Th and Ct.Po were associated with fracture.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, our results showed that Ct.Th and Ct.Po, as depicted by BDAT, exhibited significant age‐related dependence for women: Concurrent with the increased porosity, the thickness at the radius was reduced with aging. These results are consistent with data obtained previously with HRpQCT . Second, Ct.Th and Ct.Po were associated with fracture.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with data obtained previously with HRpQCT. (10,56,(59)(60)(61)(62)(63) Second, Ct.Th and Ct.Po were associated with fracture. There are no equivalent studies comparable to ours; however, many cross-sectional and retrospective studies have evaluated the association of HRpQCTderived cortical structural variables, Ct.Th and Ct.Po, measured at the ultradistal radius, with odds of prior fracture in women.…”
Section: Discussionmentioning
confidence: 99%
“…(For comparison, postmenopausal women had a 4% to 8% increase in cortical porosity of the distal tibia over 2 years in a clinical trial (9) and 300% higher cortical porosity when compared with premenopausal women in a cross-sectional study. (10) ) However, it should be kept in mind that this technology is not examining the vertebrae or femoral neck, where comparatively greater (5% to 10%) losses appear to occur as assessed by DXA; the distal tibia is not specifically examined by DXA.…”
mentioning
confidence: 99%
“…Em seguida, foram analisadas a partir do método semiquantitativo de Genant (Genant et al, 1993). (Fuller et al, 2015;Alvarenga et al, 2017). Para análise dos parâmetros de densidade e estrutura, foi utilizado o software "Standard analysis".…”
Section: Avaliação Laboratorial Do Perfil Bioquímico Do Metabolismo óunclassified
“…Um software de segmentação automática chamado "Advanced cortical analysis" foi utilizado para determinar a porosidade cortical (Ct.Po) (Alvarenga et al, 2017).…”
Section: Avaliação Laboratorial Do Perfil Bioquímico Do Metabolismo óunclassified